Medical and social prognosis for patients with perceived hypersensitivity to electricity and skin symptoms related to the use of visual display terminals - Stenberg, Berndt; Bergdahl, Jan; Edvardsson, Berit; Eriksson, Nils; Lindén, Gerd; Widman, Lars (Scandinavian Journal of Work, Environment & Health, 2002)
' ' OBJECTIVES ': 'This study attempted to give a medical and social prognosis for patients with perceived "electrical sensitivity". ' ' METHODS ': 'In 1980-1998, 350 patients with electrical sensitivity were registered at the University Hospital of Northern Sweden in Umeå, Sweden. Those with hypersensitivity to electricity had multiple symptoms evoked by exposure to different electric environments. Those with skin symptoms related to the use of visual display terminals (VDT) predominantly had facial skin symptoms evoked by a VDT, television screens, or fluorescent light tubes. A questionnaire on civil status, current health status, care, treatment and other measures taken, consequences of the problem, eliciting factors, and current employment was sent to all the patients. The response rate was 73%. Of the 50 respondents with hypersensitivity to electricity, 38% were men and 62% were women. Of the 200 patients with skin symptoms related to VDT use, 21.5% were men and 78.5% women. ' ' RESULTS ': 'More women than men had turned to caregivers, including complementary therapies. A larger proportion of patients with hypersensitivity to electricity (38%) than those with skin symptoms related to VDT use (17%) were no longer gainfully employed. Both groups reported a higher symptom frequency than that reported by the the general population. Over time, the medical prognosis improved in the latter group but not in the former. ' ' CONCLUSIONS ': 'Patients with hypersensitivity to electricity, particularly women, have extensive medical problems and a considerable number of them stop working. Many patients with skin symptoms related to VDT use have a favorable prognosis. Both groups need early and consistent management.
Keywords: electricity; environmental illness; follow-up study; gender; medical prognosis; patient; perceived health; perceived hypersensitivity; questionnaire; skin symptom; social prognosis; social situation; subgroup; visual display terminal